DESTINATION DEVELOPMENT STRATEGY POTENTIAL PANCUR AJI BY THE DEPARTMENT OF CULTURE AND TOURISM SANGGAU - Apdensy E.01104067, Yesaya Risky (FISIP Universitas Tanjungpura, 2013)
The results of the study indicated that tourism strategy from Culture and Tourism Sanggau District develop the potential of attraction development strategy and then create programs that summarize the development of strategies that have been established in order to focus its activities in the development of tourism attractions Pancur Aji . The tourism development programs namely Sanggau City tourism destination development programs, tourism marketing program development, program development partnerships, program development manager of tourism resources, and program development and appreciation of community participation. Keywords: Development of destinations and attractions, Quality Improvment and Promotion of Tourism